2018
DOI: 10.3390/agronomy8100219
|View full text |Cite
|
Sign up to set email alerts
|

The Adoption of Good Practices for Pesticides and Veterinary Drugs Use among Peasant Family Farmers of Chile

Abstract: Improvements and good practices (GPs) in rural environments are often developed by peasants themselves and shared among trust-based networks. The level of adoption of GPs by peasant family farmers (PFF) has been poorly studied. This paper describes the performance and results of the innovation adoption index (InAI) and rate (InAR) which were used to estimate the adoption of GPs for pesticide and veterinary drug use by PFF from eight different regions of Chile. Surveys were conducted among 257 farmers to find o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The results are consistent with those of Mango et al (2017), who found that the awareness and adoption of water and conservation practices in South Africa varied between specific practices and that adopters could be classified into early adopters and laggards depending on the time of their adoption. Accordingly, agricultural extension agents could benefit from farmers experienced in a variety of agricultural practices to facilitate farmer-to-farmer learning, mobilization of knowledge, and the formation of effective information networks (Susaeta et al, 2018). Table 4 shows the results of logistic regression analyses using the factors affecting the awareness and the adoption of improved maize cultivation practices by local farmers.…”
Section: Awareness and Adoption Of Improved Maize Cultivation Practicesmentioning
confidence: 99%
“…The results are consistent with those of Mango et al (2017), who found that the awareness and adoption of water and conservation practices in South Africa varied between specific practices and that adopters could be classified into early adopters and laggards depending on the time of their adoption. Accordingly, agricultural extension agents could benefit from farmers experienced in a variety of agricultural practices to facilitate farmer-to-farmer learning, mobilization of knowledge, and the formation of effective information networks (Susaeta et al, 2018). Table 4 shows the results of logistic regression analyses using the factors affecting the awareness and the adoption of improved maize cultivation practices by local farmers.…”
Section: Awareness and Adoption Of Improved Maize Cultivation Practicesmentioning
confidence: 99%
“…The use of so-called good practices, such as the use of personal protective equipment and equipment that is in good condition and correctly managed and regulated, associated with the application of products with less toxicological Engenharia Agrícola, Jaboticabal, v.41, n.2, p.245-254, mar./apr. 2021 potential, can considerably reduce the problems arising from the application of these products (Susaeta et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Due to a mistake during the production process, there was a spelling error in one of the author names in the original published version [1]. The Agronomy editorial office therefore wishes to make the following correction to the paper:…”
mentioning
confidence: 99%